Population Dynamics of Microorganism and Greenhouse Gas Emission By Applying Chicken Manure in Peat Soil - Ali Pramono; Terry Ayu Adriani; A. Wihardjaka; Prihasto Setyanto (Center for Journal Management and Publication, 2016)
Peat land accumulates organic materials and emits greenhouse gas (GHG). Agricultural activities in peat land cause the subsidence of peat land surface and the loss of carbon in the form of GHG. Appropriate management of peat land for agriculture would reduce GHG emission. This research aims to understand the microorganism population dynamics and emission of GHG on the treatment of chicken manure application in peat land. The research was conducted in the GHG Laboratory of Indonesia Agricultural Environment Research Institute (IAERI) in 2012 using peat material taken from Jabiren, Central Kalimantan. The experiment was done by incubating peat soil for 2 months with the treatment of chicken manure application and without manure. The incubation experiment was conducted by using paralon PVC pipe. Parameters observed included pH, Eh, bacteria population and fungi, as well as GHG flux (CO2, CH4 and N2O). GHG samples taking method was used a sealed containment. The research result showed at the peat given chicken manure treatment, bacteria population decreased at the end of incubation; fungi population, however, increased. The application of chicken manure on peat land planted rubber trees and pineapples would reduce GHG emission by 12.8% as compared without manure application.